Evaluasi Pengalaman Pengguna Aplikasi Kebutuhan Pelanggan Internet Menggunakan Metode User Experience Questionnaire (UEQ) - Hairuman, Andika; Leandros, Riyan; Murad, Silvia Ayunda; Maryam, Siti (UNISTEK, 2025)
The User Service Needs Application (USNA) was developed by ISP-X to support the efficiency and effectiveness of internet customer service (subscriber). The main function of this application is to support company employees in managing customer history, ticketing, installation and provisioning as well as pre-/post-sales activities quickly and accurately. However, several crucial issues were found such as frequent errors, disconnections, high latency, and a confusing interface display, which triggered customer complaints and internal work constraints. Therefore, this study aims to evaluate the user experience of the USNA application to support design and functionality improvements. The methodology used is the User Experience Questionnaire (UEQ) with six assessment aspects: Attractiveness, Clarity (Perspicuity), Efficiency (Efficiency), Dependability (Dependability), Stimulation (Stimulation), and Novelty (Novelty), accompanied by open-ended questions. A total of 135 respondents provided feedback through a Likert-based questionnaire and open-ended questions, resulting in a total of >700 qualitative statements. The results showed the highest score for the Attractiveness aspect (mean: 0.23) and the lowest for Simulation and Efficiency (0.10), indicating the need for better response time and work improvement. This research aligns with the Sustainable Development Goals (SDGs) regarding infrastructure and innovation, as well as decent work and economic growth.